Comprehensive reviews on technological and life cycle environmental aspects of solar–thermal adsorption refrigerator - Jun-Ki Choi; Anup Paudel; Bipin Karki; Katie Bradley; Natalie Quinn; Amy Ciric (Resources, Environment and Sustainability)
Refrigeration has significantly enhanced human well-being but comes with notable environmental impacts, particularly due to ozone-depleting substances and hydrofluorocarbons with high global warming potential. Solar Thermal Adsorption Refrigeration (STAR) has emerged as a promising alternative, especially in rural and off-grid regions where conventional refrigeration systems face energy limitations. This paper provides a comprehensive review of recent advancements in adsorption refrigeration technologies, including novel adsorbents like activated carbon–ethanol, metal–organic frameworks (MOFs), and composite materials designed to overcome critical challenges in heat and mass transfer. A particular emphasis is placed on the size limitations of adsorbers and the thermal efficiency of working pairs. Additionally, we critically analyze the life cycle environmental impacts of adsorption refrigeration systems, evaluating their sustainability compared to conventional vapor compression technologies. Unlike previous reviews, this paper integrates both technological developments and life cycle assessments, offering a unique perspective on STAR’s viability for sustainable refrigeration solutions. Finally, we present two novel bench-scale STAR systems, compare their environmental performance to traditional systems, and highlight key design improvements that address scalability challenges.